(untitled) (Indian Journal of Arid Horticulture, 2015)
The fruit industry in Jammu and Kashmir strawberry, guava, aonla, ber, jamun and phalsa. State forms the backbone of the state’s economy and 2. Intermediate zone: - It falls between altitudes of possesses great potential for horticulture development. 500 to 1050 meter above mean sea level. The zone The horticulture sector of J&K state is most vibrant receives sufficient monsoon during summer. The sector for economic development. Area under main fruits grown in this area are citrus, peach, horticultural crops has increased from mere 12 olive, kiwi and strawberry. thousand hectares in 1953-54 to 5.58 lakh hectares. The 3. Temperate zone: - Area falling above 1050 meter major contributor to Gross domestic product of J&K is comprises this zone. This zone is also pre horticulture (Wani, 2008, Wani, 2009, ). The state is dominantly with very small irrigated area. The fruit basically a mono-cropped and rainfed economy with crops grown in the area are apple, walnut, almond, 40% area in Jammu division and 60% in Kashmir peach, apricot, cherry and pecan nuts. division.